Reusable, Green, Portable Ionogels Based on Terpyridine-Imidazole Salt for Visual Monitoring of Pork Spoilage - Yu, Mingqi (Langmuir : the ACS journal of surfaces and colloids, 2024)
Ionogels have emerged as a promising approach because they combine the advantageous properties of ionic liquids and gels. Herein, a novel gelator bearing terpyridine and imidazolium salt units was designed and synthesized, which assembled into ionogels in three ionic liquids by a heating-cooling procedure. The properties of ionogels were characterized by FT-IR, UV-vis spectroscopy, POM, XRD, and rheology, and resonance light scattering and opacity measurements were conducted to investigate the gelation kinetics. Furthermore, the ionogels incorporating pH-sensitive dyes (BTB and MR) were exploited as colorimetric sensor to monitor total volatile basic nitrogen (TVB-N) of meat at -4 °C, which can easily and reliably estimate the quality of meat by naked eye recognition, and the results demonstrated a positive correlation between the color variation and TVB-N levels. Notably, the hydrophobic ionogel indicators are more suitable for potential application at high humidity thanks to their antiswelling advantage, which could prevent the inaccurate information produced by hydrogel indicators. In addition, the ionogels could be reused up to three times as colorimetric indicators, suggesting potential applications and competitiveness. Our research sheds new light on the novel application of ionogels in the food industry